Alcohol consumption in relation to cardiovascular and non-cardiovascular mortality in an elderly male Chinese population - Xiao-Fei Ye; Chao-Ying Miao; Wei Zhang; Chang-Sheng Sheng; Qi-Fang Huang; Ji-Guang Wang (BMC, 2021)
Abstract Background We investigated the association of alcohol consumption with cardiovascular and non-cardiovascular mortality in elderly Chinese men. Methods Our participants were recruited from residents living in a suburban town of Shanghai (≥60 years of age, n = 1702). Alcohol intake was classified as non-drinkers, past drinkers (stopped drinking for ≥12 months), and current light-to-moderate (1 to 299 g/week) and heavy drinkers (≥300 g/week). Alcoholic beverages were classified as beer/wine, rice aperitif and liquor/mix drinking. Results During 5.9 years (median) of follow-up, all-cause, cardiovascular and non-cardiovascular deaths occurred in 211, 98 and 113 participants, respectively. The corresponding incidence rates were 23.6/1000, 10.9/1000 and 12.6/1000 person-years, respectively. Both before and after adjustment for confounding factors, compared with non-drinkers (n = 843), past drinkers (n = 241), but not the current light-to-moderate (n = 241) or heavy drinkers (n = 377), had a higher risk of all-cause (adjusted hazard ratio [HR] 1.90, 95% confidence interval [CI] 1.35-2.68, P = 0.0003) and non-cardiovascular mortality (HR 2.46, 95% CI 1.55-3.91, P = 0.0001). Similar trends were observed for cardiovascular mortality (HR 1.44, 95% CI 0.85-2.44, P = 0.18). In similar unadjusted and adjusted analyses, compared with the current beer/wine drinkers (n = 203), liquor/mix drinkers (n = 142), but not aperitif drinkers (n = 273), had a significantly higher risk of all-cause (HR 3.07, 95% CI 1.39-6.79, P = 0.006), and cardiovascular mortality (HR 10.49, 95% CI 2.00-55.22, P = 0.006). Similar trends were observed for non-cardiovascular mortality (HR 1.94, 95% CI 0.73-5.16, P = 0.18). Conclusions Our study showed risks of mortality associated with past drinking and liquor drinking in the elderly Chinese men.